Is ISO14001 certification of the corporate effective?. Issue 1 (6th March 2020) - Zhang, Zhaoguo; Zhang, Chi; Cao, Danting
Abstract : Purpose: At present, the number of corporates certified by ISO14001 in China is ranked first in the world. This paper aims to explore the effectiveness of ISO14001 certification and the moderating effect of financial performance and external institutional pressures on the effectiveness. Design/methodology/approach: This paper selects Shenzhen and Shanghai A-share listed companies in the heavy polluting industry from 2010 to 2017 as the research sample, and studies the impact of ISO14001 certification on corporate environmental performance and the moderating effect of financial performance and external institutional pressures. Findings: This paper finds that ISO14001 certification has a positive impact on corporate environmental performance; corporate financial performance has a positive moderating effect in the relationship between ISO14001 certification and corporate environmental performance; government regulation, industry competition and media supervision also have positive moderating effects; and corporate environmental information disclosure has not yet had a positive moderating effect. Originality/value: Most of the current empirical research on this topic are carried out in the context of developed countries, and lack empirical evidence from developing countries. This paper will help to make up for this deficiency. In addition, this paper will help explain why the effectiveness of ISO14001 certification generates variation in different corporates and under what conditions it will play a positive role.